Microscale profiling of photosynthesis‐related variables in a highly productive biofilm photobioreactor. Issue 5 (20th November 2015) - Li, Tong; Piltz, Bastian; Podola, Björn; Dron, Anthony; de Beer, Dirk; Melkonian, Michael
ABSTRACT: In the present study depth profiles of light, oxygen, pH and photosynthetic performance in an artificial biofilm of the green alga Halochlorella rubescens in a porous substrate photobioreactor (PSBR) were recorded with microsensors. Biofilms were exposed to different light intensities (50–1, 000 μmol photons m −2 s −1 ) and CO2 levels (0.04–5% v/v in air). The distribution of photosynthetically active radiation showed almost identical trends for different surface irradiances, namely: a relatively fast drop to a depth of about 250 µm, (to 5% of the incident), followed by a slower decrease. Light penetrated into the biofilm deeper than the Lambert‐Beer Law predicted, which may be attributed to forward scattering of light, thus improving the overall light availability. Oxygen concentration profiles showed maxima at a depth between 50 and 150 μm, depending on the incident light intensity. A very fast gas exchange was observed at the biofilm surface. The highest oxygen concentration of 3.2 mM was measured with 1, 000 μmol photons m −2 s −1 and 5% supplementary CO2 . Photosynthetic productivity increased with light intensity and/or CO2 concentration and was always highest at the biofilm surface; the stimulating effect of elevated CO2 concentration in the gas phase on photosynthesis was enhanced by higher light intensities. The dissolved inorganic carbon concentration profiles suggest that the availability of the dissolved free CO2 has the strongest impact on photosynthetic productivity. The results suggest that dark respiration could explain previously observed decrease in growth rate over cultivation time in this type of PSBR. Our results represent a basis for understanding the complex dynamics of environmental variables and metabolic processes in artificial phototrophic biofilms exposed to a gas phase and can be used to improve the design and operational parameters of PSBRs. Biotechnol. Bioeng. 2016;113: 1046–1055. © 2015 Wiley Periodicals, Inc. Abstract : Distribution of light intensity, oxygen concentration, pH and photosynthetic productivity of a non‐submerged algal biofilm in a porous substrate biofilm photobioreactor (PSBR) subjected to different light intensities and CO2 concentrations were profiled with microsensors. The data collected revealed the complex interactions between environmental factors (e.g. irradiance, dissolved oxygen, dissolved inorganic carbon) and biological processes (e.g. photosynthesis). Furthermore, the results provide a basis for process optimization as well as understanding the advantages of PSBRs over other types of photobioreactors.